Community outbreak of COVID-19 among people who use drugs attending a harm reduction centre in Barcelona, Spain - Nacho Sánchez-Valdivia; Maria Gabriela Barbaglia; Marc Olivella-Cirici; Noelia Girona Marcos; Mercè Gotsens; Amaia Garrido Albaina; Cristina Rius; Montse Bartroli; Gloria Pérez (BMC, 2023)
Abstract Background The COVID-19 pandemic particularly affected the health of vulnerable population, such as people who use drugs. Due to compromised baseline health status, certain drug uses and settings and socioeconomic deprivation related to poverty and homelessness, drug users faced higher risk of COVID-19 infection. They had difficulty in adhering to the public health measures (i.e. physical distancing, hand hygiene and mask use). Also, the struggle to implement non-pharmaceutical actions (i.e. test-trace-isolate-quarantine strategy) among SARS-COV-2-infected drug users and their close contacts challenged the public health response. Therefore, this study aimed to describe a community COVID-19 outbreak and its approach among drug users of a harm reduction programme in an outpatient drug treatment centre in Barcelona, Spain. Methods We conducted an observational descriptive study of an outbreak of COVID-19 among people who use drugs attending the harm reduction programme of an outpatient drug treatment centre in the city of Barcelona, between July and October 2021 (n = 440). A passive search for cases was carried out with rapid antigens tests targeting symptomatic users who attended the facilities. Results Nineteen positive COVID-19 cases were identified among symptomatic drug users, between July and October 2021, with an attack rate of 4.3%. Specific measures were taken to control the outbreak, such as offering accommodation to self-isolate in a low-threshold residential resource to homeless drug users who tested positive and intensifying the vaccination strategy. The management of the outbreak was carried out in close collaboration between the outpatient centre and the main public health stakeholders in the city of Barcelona. Conclusions This study shows the complexity of managing and investigating COVID-19 outbreaks in vulnerable population groups. Epidemiological control measures, such as the test-trace-isolate-quarantine strategy, were challenging to implement due to technology-related barriers and socioeconomic vulnerabilities, especially homelessness. Community-based interventions, cooperation among stakeholders and housing-related policies were helpful in tackling outbreaks among people who use drugs. When addressing vulnerable and hidden populations, the perspective of inequalities should be included in epidemiological surveillance and outbreak control strategies.